Towards a code of ethics for teaching at second-level in Ireland - Mac Daid, Declan (Trinity College (Dublin, Ireland). School of Education, 2010)
The thesis explored the nature of teaching and its possible moral and ethical underpinnings. It also examined and outlined codes of ethics, codes of ethics in teaching internationally and the current position in Ireland regarding ethics in teaching. Taking into account the nature of teaching, the common threads of the main schools of teaching historically and of the schools of moral philosophy, it then offered a draft code of ethics for teaching in Ireland, placed within the present setting, history and context of teaching in Ireland.
Keywords: Education, D.Ed.; Ph.D. Trinity College Dublin